Lipopolysaccharide enhances ADAR2 which drives Hirschsprung's disease by impairing miR‐142‐3p biogenesis. Issue 9 (29th June 2018) - Peng, Lei; Zhang, Hua; Su, Yang; Shen, Qiyang; Du, Chunxia; Xie, Hua; Li, Hongxing; Yan, Jin; Shen, Ziyang; Jiang, Weiwei; Xia, Yankai; Xu, Xiaoqun; et al.
Abstract: Researches over the past decade suggest that lipopolysaccharide is a dominant driver of gastrointestinal motility and could damage the enteric neuron of rat or porcine. However, it remains poorly defined whether LPS participates in Hirschsprung's disease (HSCR). Here, we discovered that LPS increased in HSCR tissues. Furthermore, LPS treatment suppressed the proliferation and differentiation of neural precursor cells (NPCs) or proliferation and migration of human 293T cells. ADAR2 (adenosine deaminase acting on RNA2)‐mediated post‐transcriptional adenosine‐to‐inosine RNA editing promotes cancer progression. We show that increased LPS activates ADAR2 and subsequently regulates the A‐to‐I RNA editing which suppresses the miR‐142 expression. RNA sequencing combined with qRT‐PCR suggested that ADAR2 restrain cell migration and proliferation via pri‐miR‐142 editing and STAU1 up‐regulation. In conclusion, the findings illustrate that LPS participates in HSCR through the LPS‐ADAR2‐miR‐142‐STAU1 axis.